Mobile-Based Elementary School Report Card Information System (SIRAM) to Reduce Teacher Stress Levels - Fikrivenia Ayu Farisa; I Gede Margunayasa (Journal of Psychology and Instruction, 2022)
The conventional report cards that are used still have a high level of complexity, thus triggering the teacher's stress level at the end of each semester in inputting grades. The purpose of this study was to create a mobile-based elementary school report card information system (SIRAM) to reduce teacher stress levels. This development research uses the ADDIE model. In this study using a quantitative approach as well as qualitative. The research subjects were grade 3 (three) teachers. Methods of data collection using interviews, observation guidelines, questionnaires, and rating scale sheets. The data analysis technique used the one sample t-test. Based on the analysis carried out, the results of the SIRAM application have Login, Create, Read, Update, Delete (CRUD) features. The result of content validity is 0.9, so that it is declared valid with a high level of validity indicating that it is feasible to use it. The results of the effectiveness test of the teacher's stress level, with a significance level of 0.05 (5%) obtained a t value of 1.761, then the SIRAM application did not affect the teacher's stress level, before and after the administration of the SIRAM application. The implication of this research is that it is hoped that the next impact will be that schools can subscribe to hosting as a support for applications so that they can continue to use the SIRAM application in the future.